2016
DOI: 10.1111/joms.12211
|View full text |Cite
|
Sign up to set email alerts
|

‘Who Knows What?’ in New Venture Teams: Transactive Memory Systems as a Micro‐Foundation of Entrepreneurial Orientation

Abstract: The increasing importance of entrepreneurial behaviour has led scholars to embrace the idea that an entrepreneurial orientation (EO) is an important predictor of firm performance. While EO occupies a central position in strategic entrepreneurship research, scholars have yet to explore its origins in new ventures. Drawing on the knowledge-based and cognitive views, we theorize that a new venture team's transactive memory system is a cognitive mechanism that spurs the development of an EO. In a field study of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 92 publications
(122 reference statements)
1
75
0
Order By: Relevance
“…Paralleling earlier findings (Dai et al 2016), we observe that these trust-based relations stimulated a willingness to change and to engage in collective action. In view of these close ties and open interaction, all teams experienced a specific shared moment of transition (SMT), a lifechanging moment, in which both the idea to jointly create a venture was made and the framework for how this venture should be developed was formed.…”
Section: Shared Moments Of Transitionsupporting
confidence: 88%
“…Paralleling earlier findings (Dai et al 2016), we observe that these trust-based relations stimulated a willingness to change and to engage in collective action. In view of these close ties and open interaction, all teams experienced a specific shared moment of transition (SMT), a lifechanging moment, in which both the idea to jointly create a venture was made and the framework for how this venture should be developed was formed.…”
Section: Shared Moments Of Transitionsupporting
confidence: 88%
“…A wider implication of this finding about the positive moderating effect of CEO-TMT tenure overlap (see Figure 4) derives from the notion of shared leadership in long tenured teams (D'Innocenzo, Mathieu, & Kukenberger, 2014). Studies have shown that team longevity is associated with the development of converged mindsets (Dai et al, 2016) and collective leadership processes (Fischer, Dietz, & Antonakis, in press;Hoch, 2013;Kunze et al, 2016) that allow the group's leader to promote collective decision making behavior. In teams with strong knowledge subgroups, the development of task-based mental models (Mathieu et al, 2000) and leadership processes are of fundamental importance, as they act as a common platform of communication between subgroups, and help the entire team to enhance its collective information processing potential and performance (Gratton et al, 2007;Kearney & Gebert, 2009).…”
Section: Resultsmentioning
confidence: 85%
“…First, research shows that overlapping team tenure allows members of a team to "develop a shared conceptualization of 'who knows what' " in the group (Brandon & Hollingshead, 2004: 633), and allocate tasks to those who possess the required expertise (Dai, Roundy, Chok, Ding, & Byun, 2016). According to the resource-allocation model, effective team leaders are those who are aware of the information and skills that reside in the group, and can allocate resources in a way to enhance overall team performance (Kanfer, Ackerman, Murtha, Dugdale & Nelson, 1994).…”
Section: Ceo-tmt Shared Experience Research On Organizational Behavimentioning
confidence: 99%
“…Proactive supply chain partners can achieve first-mover advantages by bringing innovative products to market before the competition (Dess & Lumpkin, 2005;Lieberman & Montgomery, 1988). Pro-activeness requires the accurate sensing of shifts in the marketplace and developing corresponding action plans (Dai et al, 2016). Proactive supply chain partners can develop systems to monitor market trends, sense future customer needs, and predict changes in marketplace demand (Dess & Lumpkin, 2005).…”
Section: Entrepreneurial Orientation and Dynamic Supply Chain Capabilmentioning
confidence: 99%